A novel fault tolerant scheme and reliability modeling for a wireless modular prosthetic limb - Saeed, Mayar Mohamed (AUC Knowledge Fountain, 2020)
This thesis presents a study for a wireless scheme for the Johns Hopkins modular prosthetic limb (MPL) as well as a demonstration for a novel fault tolerant scheme to further improve the arm’s reliability. Currently, the innovative prosthetic limbs that depend on Network Control Systems are wired devices which have two main disadvantages; the wear and tear issue as well as the mobility limitation problem. Hence, the same function can be done by replacing the wired models by Wireless Body Area Networks (WBANs) in order to avoid the wear and tear and mobility issues. Furthermore, the prosthetic limbs are life-saving and real time medical devices which demand high reliability as failure may lead to harsh consequences. The reputable Modular Prosthetic Limb (MPL) that is developed by Johns Hopkins applied physics laboratory is revisited in this thesis. Using RIVERBED, the wireless scheme of the Johns Hopkins arm is studied as well as a fault-tolerant model for the same arm. All scenarios undergo interference analysis and a 95% confidence analysis. The simulation results have demonstrated that the end-to-end delays are below the system’s deadlines and there is zero packet loss in all scenarios; thus, the system requirements are satisfied. Further, the reliability of the system was calculated by modelling several scenarios using SHARPE. It has been proven that a system that uses a supervisor with lower specifications will have a very close reliability values to the system that uses very powerful supervisor if it was repaired after the failure of the third controller. Finally, it was proved that the motor redundancy has significantly enhanced the reliability.